Sea-Level Rise and Psychological Distress among Coastal Communities: Insights from the Southwest Coast of Bangladesh - Kabir, Syed Muhammad Sajjad (Curtin University, 2023)
This research provides the first empirical investigation of sea-level rise (SLR) induced environmental stressors on psychological health. Following a systematic review, longitudinally examined the association between SLR and psychological health before and after the monsoon season among coastal communities in Bangladesh. SLR-induced stressors were associated with resource loss, which in turn enhanced distress, depression, anxiety, and stress. Findings highlighted a need for psychosocial support and call for interventions amidst the growing threat of climate change.